T.E. Lawrence and the Arab Revolt (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article explores Lawrence's entrance into the Arab Revolt, his role in the movement, and how it affected Lawrence personally. Moreover, it argues that Lawrence's asceticism allowed him to relate to the Bedouin in such a way to engender respect and lead them to victory. At the same time, it also illustrates the effect of transculturation on Lawrence and his inability to identify with either culture in the end.